(untitled) (Swiss Medical Weekly, 2016)
AIMS OF THE STUDY: To assess the cost-effectiveness of primarily surgical treatment (PST) versus primarily conservative treatment (PCT) in adults with intermediate severity, acute or subacute, lumbar radicular syndrome due to intervertebral disc herniation. METHODS: A decision analytic model from healthcare system and societal perspectives was used to compare outcomes and costs of PST with those of PCT (physiotherapy, epidural injection and medication). Treatment pathways and quality of life were obtained from published clinical trials. Costs were derived from Swiss health insurance claims data. Swiss clinical experts provided information on use of medication and physiotherapy. The main outcome of interest was incremental cost per quality-adjusted-life-year (QALY) gained over a period of 2 years. Costs and QALYs gained were discounted from the second year, at a rate of 2% per year. RESULTS: In the base-case analysis from a healthcare system perspective, over 2 years, PST compared with PCT led to 0.0634 additional QALYs per person, at an additional net cost of CHF 7198 per person. The corresponding incremental cost effectiveness ratio (ICER) amounted to CHF 113 396 per QALY gained. From a societal perspective the ICER was CHF 70 711 per QALY gained. ICERs were subject to substantial uncertainty because of limitations in available data. CONCLUSION: A PST approach, when compared with PCT, may be cost effective from a societal perspective based on a willingness-to-pay threshold of CHF 100 000 per QALY gained. However, it is less likely to be cost effective from the perspective of the Swiss healthcare system. More research is needed to understand the long-term economic implications among this patient group.